(untitled) (Legal journal - Research in Legal and Social Sciences, 2021)
This investigation is a general review of relevant contents related to the setting up of positive norm departing from statements, resolutions, and action plans agreed at an international level by the States in summits, congresses, conventions and other mechanisms they find as members of international organizations. These forums discuss current judicial topics and propose solutions to different types of conflict that may arise at international level. Nevertheless, they are non-binding, since they are suggested principles to be adopted. In this context, this paper covers an analysis of the case Salvatore Grimaldi, brought to the European Court in accordance with the application of soft law. The case is about an Italian immigrant who suffered of a disease in the hands which was not included in the list of occupational diseases in Belgium. Therefore, he could not be compensated as employee with the mentioned illness. The case is of the utmost importance since these mechanisms constitute to convert the case into hard law, that is to say, in positive binding normative and although the effects will be indirect, they are found to be as effective as the law itself, for they are adopted by jurisprudence in law courts in the member states.